Essential Infantile Esotropia: A Course of Treatment From Our Experience - Pensiero, Stefano; Diplotti, Laura; Presotto, Marianna; Ronfani, Luca; Barbi, Egidio (Frontiers in Pediatrics, 2021)
Background. Essential infantile esotropia is the most common type of childhood esotropia. Its classical approach is surgical, though, less invasive techniques have been proposed as an adjunct or alternative to traditional surgery. Among them, chemodenervation with botulinum toxin have been investigated, showing variable and sometimes conflicting results. Objectives. To compare the outcomes of bilateral botulinum toxin injection and traditional surgery in a pediatric population with essential infantile esotropia, in order to optimize and standardize the therapeutic approach. Other purposes are to evaluate whether early intervention may prevent the onset of vertical ocular deviation (which is part of the clinical picture of essential infantile esotropia) and/or influence the development of fine stereopsis; and to assess changes in refractive status over time among the enrolled population. Methods. A retrospective consecutive cohort study was conducted in 86 children aged 0-48 months who underwent correction of essential infantile esotropia. The primary intervention in naïve subjects was either bilateral botulinum toxin injection (36 subjects, “BT group”) or strabismus surgery (50 subjects, “surgery group”). Results. Overall, botulinum toxin chemodenervation (1 or 2 injections) was effective in 13 (36.1%) subjects. With regards to residual deviation angle, the outcomes at least 5 years after the last intervention were overlapping in children receiving initial treatment with either injection or surgery; though, the success rate of primary intervention in the surgery group was higher, and the average number of interventions necessary to achieve orthotropia smaller. Both early treatment with chemodenervation and surgery at a later age were not found to prevent the onset of vertical ocular deviation, whereas, surprisingly, the percentage of subjects developing fine stereopsis was higher in the surgery group. Finally, as regards the change in refractive status over time, most of the subjects increased their initial hyperopia, while 10% became myopic. Conclusions. Our data suggest that a single bilateral botulinum toxin injection by age 2 years should be considered as the first line treatment of essential infantile esotropia without vertical component; while, traditional surgery should be considered as the first line treatment for all other cases and in subjects unresponsive to primary single botulinum toxin injection